Scholarly Viewpoints - Tarling, Nicholas (Penerbit Universiti Sains Malaysia (USM Press), 2012)
The nation-state paradigm for writing history—which goes back to Leopold von Ranke and the foundation of the modern discipline —was sometimes dismissed in the late 20th century when the state was supposed, amid economic and cultural "globalisation," to be withering away. But it is still very much alive in areas where the nation-state is still establishing itself as the pre-eminent political entity. And that includes much of the "Asia Pacific." ASEAN is built on the Bandung principles that endorsed sovereignty and non-intervention. Japan was the first "modern" state in East Asia. China has, perhaps, a more ambiguous attitude. New Zealand—if not Australia, too—is very much into navel-gazing. Indeed it sometimes seems that neighbours are reluctant to write about neighbours. Language is often a barrier, but sensitivity perhaps even more often. Those who write about "regions" tend to be "outsiders" especially students of politics and "security." Historians are more cautious. The archives they need are often closed and they wonder whether a region has reality